An Overview of the Technological Progress in Propellants Using Hydroxyl-Terminated Polybutadiene as Binder During 2002-2012 - Rufino,Simone Carvalho (2013)
ABSTRACT: The purpose of this article is to present a study on the technological development of propellants, which are used in solid and hybrid rocket motor, that have been employing hydroxyl-terminated polybutadiene (HTPB) as a binder, for the past ten years. The results prove that major research conducted on propulsion technologies continues using HTPB as a binder, with China and the United States being the countries with greater publications, and Brazil appearing at the fifth position in the ranking. The scientific and technological information was collected from articles, conference papers, reviews (over the last ten years) and patents granted in the United States by scientific and USPTO patent databases.